2019
DOI: 10.1080/09638288.2019.1603328
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of behavioural interventions on physical activity levels after hip or knee joint replacement: a systematic review

Abstract: Structured summaryProvide a structured summary including, as applicable: background; objectives; data sources; study eligibility criteria, participants, and interventions; study appraisal and synthesis methods; results; limitations; conclusions and implications of key findings; systematic review registration number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(40 citation statements)
references
References 21 publications
2
37
1
Order By: Relevance
“…Prior literature has shown that comorbidities, whether assessed individually or by using validated indices [ 39 , 40 ], are associated with poor functional outcome after THR. In people with OA, comorbidities such as respiratory and cardiovascular disease have been linked with lower physical activity levels, compared to those without significant comorbidities [ 41 ] and current evidence demonstrates that activity levels do not improve after THR [ 42 , 43 ]. This suggests a role for increasing physical activity in patients with significant comorbidities prior to undergoing THR to maximise post-operative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature has shown that comorbidities, whether assessed individually or by using validated indices [ 39 , 40 ], are associated with poor functional outcome after THR. In people with OA, comorbidities such as respiratory and cardiovascular disease have been linked with lower physical activity levels, compared to those without significant comorbidities [ 41 ] and current evidence demonstrates that activity levels do not improve after THR [ 42 , 43 ]. This suggests a role for increasing physical activity in patients with significant comorbidities prior to undergoing THR to maximise post-operative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For 1:1-gf-sub, Figure 6 shows that both peak positions and intensity change continuously. Bond distance of B [3] -O decreases from 1.45 Å to 1.41 Å to 1.38 Å and the bond distance of B [4] -O decreases from 1. F I G U R E PDF of B-O and the deconvolution of B [3] -O and B [4] -O of 6P55 with (A) 5, (B)10, and (C)15% B 2 O 3 /SiO 2 substitutions…”
Section: The Effect Of B 2 O 3 To Sio 2 Substitution On the Short-ran...mentioning
confidence: 93%
“…In 1:1-gf-sub (black), B 3 and B 4 converting to B 2 and even B 1 . However, we must consider the change of SiQ n species because of F I G U R E 1 9 B [3] and B [4] of (A) 1:1-gf-sub series and (B) 1:2-gf-sub from 498 to 2298 K. (C) Snapshot of 𝐵 [3] 2 and (D) 𝐵 [4] 3 from MD simulations the additional glass formers (as shown in Figure 18D). 1:2gf-sub shows a relatively steady amount of SiQ 3 , while 15% of SiQ 2 converts to SiQ 4 with increase of B 2 O 3 /SiO 2 , which reduces the T g .…”
Section: Influence Of B 2 O 3 Substitution To the Thermal Properties ...mentioning
confidence: 99%
See 2 more Smart Citations